THE RELATION BETWEEN HEALTH KNOWLEDGE AND “BSE” ATTITUDE AS AN EFFORT FOR EARLY DETECTION OF BREAST CANCER IN YOUNG WOMEN AT HIGH SCHOOL 1 KETAPANG, SOUTH LAMPUNG 2022 - Anggiyanti, Finisia; Santosa, Puji Raharja; Dinda Nur Fajri Hidayati Bunga (Soscience: Jurnal Ilmu Sosial Science, 2024)
Breast cancer ranks first of all cancers that occur in women. Currently, most breast cancer sufferers are young, not even a few are 14 years old and in Indonesia more than 80% of cases are found to be in an advanced stage, where treatment is difficult to do this is due to low health knowledge about early detection of breast cancer. . Early detection of breast cancer can be done by doing BSE. The purpose of this study was to determine the relationship between health knowledge and the attitude of "BSE" as an effort to detect breast cancer in adolescent girls at SMAN 1 Ketapang, South Lampung. The research method used by the researcher is analytic observational by using a cross sectional design. In this study using a questionnaire instrument, the samples used as respondents by the researchers were 86 young women at SMAN 1 Ketapang, South Lampung. The results showed that the p-value (0.000) < value (0.05). This shows that H0 is rejected and Ha is accepted. Based on the results of the study, there is a significant relationship between health knowledge and the attitude of "BSE" as an effort to detect breast cancer in adolescent girls at SMAN 1 Ketapang, South Lampung.